Using the Unified Theory of Acceptance and Use of Technology to Explain E-commerce Acceptance by Jordanian Travel Agencies - Dajani, Dima (Journal of Comparative International Management, 2016)
This study examines the possibility of adapting a technology acceptance model designed in the context of the developed world to a developing nation. Jordan will be used as a case study for this purpose because it experiences similar challenges and opportunities that other Arab countries encounter in their technology acceptance. Qualitative and quantitative techniques were used to collect data for this research. The results indicated that performance expectancy, effort expectancy, social influence, competitive pressure and facilitating conditions had a positive impact on intention to use e-commerce. In contrast, perceived risk, government support and compatibility had insignificant relationship with behavioral intention. Furthermore, the result pointed out that age and gender did not affect the relationship between performance expectancy, perceived risk and behavioral intention.